2021
DOI: 10.2217/pmt-2021-0013
|View full text |Cite
|
Sign up to set email alerts
|

Physical, Emotional and Social Pain Communication by Patients Diagnosed and Living with Multiple Myeloma

Abstract: Aim: To describe physical, social and emotional aspects of pain self-reported by patients with multiple myeloma (MM), and patient–physician communication of physical pain. Materials & methods: We analyzed self-reported data from 330 adults receiving anti-MM therapy in Germany and Italy on health-related quality of life (European Organisation for Research and Treatment of Cancer Quality of Life Core-30 Questionnaire version 3, -MY20) and bone pain symptoms. Results: Patients experienced clinically important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Similarly, a comparison of palliative care patient-reported EORTC QLQ-C30 with a proxy QoL questionnaire completed by physicians has illustrated that physicians’ perception of their patients’ HRQoL may be clinically different from the patients’ own assessment [ 34 ]. A study evaluating self-reported pain also showed a discordance between the perceptions of MM patients compared with physicians, with nearly half of physicians underestimating bone pain severity, possibly reflecting the lack of time, experience, and tools available to physicians to assess the full impact of symptoms on patients [ 35 ]. Furthermore, differences in patient and physician perspectives may also be influenced by patients’ level of health literacy, which can in turn be enhanced by improved patient-physician communication [ 6 , 32 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a comparison of palliative care patient-reported EORTC QLQ-C30 with a proxy QoL questionnaire completed by physicians has illustrated that physicians’ perception of their patients’ HRQoL may be clinically different from the patients’ own assessment [ 34 ]. A study evaluating self-reported pain also showed a discordance between the perceptions of MM patients compared with physicians, with nearly half of physicians underestimating bone pain severity, possibly reflecting the lack of time, experience, and tools available to physicians to assess the full impact of symptoms on patients [ 35 ]. Furthermore, differences in patient and physician perspectives may also be influenced by patients’ level of health literacy, which can in turn be enhanced by improved patient-physician communication [ 6 , 32 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite adherence with denosumab being generally high across the initiation, implementation, and persistence phases, there is scope for adherence to be improved. Some potential strategies are summarized in Table 3 [35][36][37][38]. Strategies to improve medication adherence may reduce avoidable hospitalizations and improve patient quality of life, with resulting cost savings [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, associations between the particular dimensions of total pain and psychological outcomes have been found. For example, stronger physiological and psychological pain symptoms are associated with lower levels of physical, social, and emotional well-being among patients treated for cancer pain [13]; greater emotional and social pain are related to lower quality of life and increasing disease severity in hematological malignancies [14]; and more intense spiritual pain is related to poorer coping abilities and higher levels of depression, anxiety, and worry [15]. On the other hand, total pain is positively associated with stress and personal activities aimed at searching for meaning [10,12].…”
Section: Associations Between Total Pain and The Fear Of Recurrencementioning
confidence: 99%